A new species of flightless Hadromeropsis from the Colombian páramo (Coleoptera: Curculionidae; Entiminae; Tanymecini) - Anderson, Robert S. (Zootaxa, 2008)
During a visit to the New Zealand Arthropod Collection in Auckland, New Zealand, in February 2007 I examined a series of specimens of a large flightless species of Entiminae from high elevation in the páramo of Colombia. To my surprise, they proved to represent an undescribed species of Tanymecini. This species is here described as Hadromeropsis annae Anderson, in recognition of the 80th birthday (19 July 2007) of Anne T. Howden, of Ottawa, Canada. The genus Hadromeropsis was last revised by Anne Howden in 1982. Description of this species in her honor is a fitting testament to her excellent work on Tanymecini.